Deslocalizaciones internacionales: impacto sobre la estructura manufacturera española (1995-2005) - GUTIÉRREZ SOBRAO, David (Papeles de Europa, 2011)
The study that follows focuses on the impact of international offshoring process on the Spanish economy. We delimit the field of study to the manufacturing activity because it is here where these processes have been more intense, and also for its key role in the whole economic structure. The chosen time period is 1995-2005, for reasons associated with the availability of data. We apply a structural approach and wonder about qualitative changes in Spanish manufacturing induced by international offshoring. Our working hypothesis is that international offshoring has hit hardest in areas of high technology, contributing to a maintenance of Spanish industrial specialization pattern.
Keywords: Offshoring; Manufacturing structure; Spain